Asymptomatic Primary Fallopian Tube Cancer: An Unusual Cause of Axillary Lymphadenopathy - N. A. Healy; S. O. Hynes; J. Bruzzi; S. Curran; M. O'Leary; K. J. Sweeney (Case Reports in Obstetrics and Gynecology)
Primary Fallopian tube malignancy is considered a rare disease and is often mistaken histologically and clinically for ovarian cancer. The etiology is poorly understood, and it typically presents at an advanced disease stage, as symptoms are often absent in the initial period. As a result, primary fallopian tube cancer is generally associated with a poor prognosis. We present the case of a 45-year-old female who presents with a 5-day history of left axillary swelling and a normal breast examination. Mammogram and biopsy of a lesion in the left breast revealed a fibroadenoma but no other abnormalities. Initial sampling of the axillary node was suspicious for a primary breast malignancy, but histology of the excised node refuted this. PET-CT showed an area of high uptake in the right pelvis, and a laparoscopy identified a tumor of the left fallopian tube which was subsequently excised and confirmed as a serous adenocarcinoma.